Kyrgyz Republic Public Expenditure Review Policy Notes : Education - World Bank (Washington, DC, 2014)
The Kyrgyz Republic has seen a rapid expansion of public spending on education in recent years, yet the sector continues to be plagued by a number of challenges. Efficiency of spending is low across the education system, and sustainability of sector financing is threatened by large outlays on wages following rapid wage growth during 2010-2012 and high shares of resources going toward food and utility costs. Lack of investment in the necessary teaching and learning materials contributes to low education quality, with over 80 percent of 15 year olds scoring at "functionally illiterate" levels in the 2009 PISA assessment. Coverage remains low in pre-primary education, while equity of education service provision varies widely across localities and social groups. The practices surrounding education sector governance could also be improved and brought in line with international standards. This chapter is composed of six sections. Section two presents an overview of the Kyrgyz education sector, covering its structure and governance, demand for education services, and recent spending trends. Section three discusses disparities in access, quality, and public spending across localities and social groups. Section four analyzes the efficiency and sustainability of education sector spending. Section five looks at determinants of education quality and options for their improvement. Section six concludes and offers concrete policy recommendations for sector reform.